In Vitro Efficacy of Curcuma longa in Combating Staphylococcus aureus Subclinical Mastitis in Buffalo - Singh, Ankur; Singh, Satyavrat; Singh, Jitendra Pratap; Kumar, Rajesh; Singh, Naveen Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Subclinical mastitis (SCM) being hidden, goes unnoticed until diagnosed in the lab and is therefore the most studied type of mastitis engaging  researchers to look for efficient therapeutic or preventive modalities. The in-vitro efficacy of aqueous, methanolic and hydro-methanolic extracts  of Curcuma longa was studied against isolates of S. aureus from SCM cases of buffaloes. The stock solution at the concentrations of 50 (HM-50),  100 (HM-100), 150 (HM-150), 200 (HM-200) and 250 (HM-250) mg/mL was used to prepare the disc. Enrofloxacin disc was used as standard. The  highest zone of inhibition (8.2 mm, and 10.1 mm) was noted with the concentration 250 mg/disc of aqueous and methanolic extracts of Curcuma  longa, respectively. The hydro-methanolic extract failed to yield zone of inhibition against S. aureus at all five concentrations. It can be concluded  that the antimicrobial potential of aqueous and methanolic extract of Curcuma longa can be used in the treatment or prevention of mastitis.
Keywords: Buffalo; Curcuma longa; Subclinical mastitis